Surgical candidacy and treatment initiation among women with cervical cancer at public referral hospitals in Kampala, Uganda: a descriptive cohort study. Issue 12 (12th December 2020) - Swanson, Megan; Nakalembe, Miriam; Chen, Lee-may; Ueda, Stefanie; Namugga, Jane; Nakisige, Carol; Huchko, Megan J
Abstract : Objectives: This study aimed to report the proportion of women with a new diagnosis of cervical cancer recommended for curative hysterectomy as well as associated factors. We also report recommended treatments by stage and patterns of treatment initiation. Design: This was an observational cohort study. Inperson surveys were followed by a phone call. Setting: Participants were recruited at the two public tertiary care referral hospitals in Kampala, Uganda. Participants: Adult women with a new diagnosis of cervical cancer were eligible: 332 were invited to participate, 268 met the criteria and enrolled, and 255 completed both surveys. Primary and secondary outcomes measures: The primary outcome of interest was surgical candidacy; a secondary outcome was treatment initiation. Descriptive and multivariate statistical analyses examined the associations between predictors and outcomes. Sensitivity analyses were performed to examine outcomes in subgroups, including stage and availability of radiation. Results: Among 268 participants, 76% were diagnosed at an advanced stage (IIB–IVB). In total, 12% were recommended for hysterectomy. In adjusted analysis, living within 15 km of Kampala (OR 3.10, 95% CI 1.20 to 8.03) and prior screening (OR 2.89, 95% CI 1.22 to 6.83) were significantly associated with surgical candidacy. Radiotherapy availability was not significantly associated with treatment recommendations for early-stage disease (IA–IIA), but was associated with recommended treatment modality (chemoradiation vs primary chemotherapy) for locally advanced stage (IIB–IIIB). Most (67%) had started treatment. No demographic or health factor, treatment recommendation, or radiation availability was associated with treatment initiation. Among those recommended for hysterectomy, 55% underwent surgery. Among those who had initiated treatment, 82% started the modality that was recommended. Conclusion: Women presented to public referral centres in Kampala with mostly advanced-stage cervical cancer and few were recommended for surgery. Most were able to initiate treatment. Lack of access to radiation did not significantly increase the proportion of early-stage cancers recommended for hysterectomy.